Evaluasi Keseragaman Klonal Enam Klon Kakao Unggul Berdasarkan Marka SSR - Sulistiyorini, Indah; Rubiyo, Rubiyo; Sudarsono, Sudarsono (Jurnal Tanaman Industri dan Penyegar, 2018)
Propagation of cacao plants is generally carried out vegetatively. Therefore, plants that are clonally propagated should be genetically uniform. Genetic uniformity in cacao clones is also very important information for germplasm conservation and in obtaining pure parental crosses. Evaluation of genetic uniformity can be seen through analysis using SSR markers. This study aimed to determine the genetic uniformity in six cacao clones using SSR markers. This experiment was conducted at IIBCRI Integrated Laboratory in Sukabumi and Plant Molecular Biology Laboratory, IPB Bogor, from September 2015 to December 2016.  Six cacao clones used (TSH 858, TSH 908, ICS 13, PA 300, GC 7 and UIT) are from Kalitelepak experimental station of  PTPN XII, Genteng District, Banyuwangi, East Java.  Ten samples were taken randomly to represent cacao clones. DNA amplification was carried out using 12 SSR markers. The result showed that 12 SSR markers generated 45 alleles with the number of alleles per locus was 3-4 alleles. The polymorphic information content (PIC) ranges from 0.37–0.67, which are identied as very informative molecular analysis in identifying the genetical uniformity of the evaluated cacao population. Six SSR loci generated variant alleles within both the TSH 858 and UIT clones, indicating there are off-type plants in these two samples. Clonal uniformity were detected for samples of the GC 7, ICS 13, PA 300 and TSH 908 clones. On the other hand, 8.33% of evaluated samples within the TSH 858 and UIT clones were off-type plants.